EFFECT OF NEEM LEAF ON NITRIFICATION AND SELECTED PROPRETIES OF SOIL AMENDED WITH DIFFERENT SOURCES OF NITROGEN - Sivasakthy, K.; Gnanavelrajah, N. (Journal of Science and Management, 2010)
A laboratory incubation study was carried out in Calcic Red Yellow Latosols fertilized with urea, compost and poultry manure to find out the effect of different N sources with locally available potential nitrification inhibitor on nitrification, microbial biomass and other properties of soil. N sources were applied at the rate of 200mg N/Kg soil. Treatments were T1 (urea), T2 (compost), T3 (poultry manure), T4 (urea + neem leaf powder), T5 (compost + neem leaf powder) and T6 (poultry manure + neem leaf powder). Complete randomized design was used with three replicates. Results indicated that addition of neem leaf powder significantly reduced NO3– content with all three nitrogen sources. Percentage reductions of nitrification by neem leaf powder with urea, compost and poultry manure were 53.85, 62.5 and 57.14 respectively. Lowest (28 mg/Kg soil) NO3-- N content was measured in T5 (compost + neem leaf powder) and T6 (poultry manure + neem leaf powder) and highest (121 mg/Kg soil) in T1 (urea). Cation exchange capacity of soil significantly increased in organically treated soils compared to inorganically treated soils. Highest (2510µg/g) microbial biomass carbon was measured in T3 (poultry manure) and lowest (930µg/g) in T1 (urea) on dry weight basis. Results therefore indicate that, organic sources improve soil fertility parameters and reduce NO3- pollution risk compared to inorganic fertilizer. Moreover, neem leaf powder has potential to reduce nitrification with both organic and inorganic sources.
Keywords: Nitrification; Urea; Compost; Poultry Manure